Contemporary research on business and management : proceedings of the International Seminar of Contemporary Research on Business and Management (ISCRBM 2020), 25-27 November, 2020, Surabaya, Indonesia /: proceedings of the International Seminar of Contemporary Research on Business and Management (ISCRBM 2020), 25-27 November, 2020, Surabaya, Indonesia. (2021) - Unknown
No abstract available